Estresse e sintomas em profissionais de enfermagem de um hospital universitário - (:unkn) unknown (Universidade Federal do Amazonas, 2014)
Due to the demands of the globalized capitalist world, we observe a change in patterns of health and disease. Currently, stress is considered a global epidemic defined as a state of tension related to disruption of homeostasis may trigger beneficial or harmful organic reactions, physical, psychological or physical-psychological character. Working conditions experienced by nursing staff in the hospital environment, configure it as an exhausting and stressful profession which lead to impaired quality of care. Therefore, these are early diagnosis and interventions for development of chronic stress not required and hence the burnout. In this sense, we sought to identify the occurrence of stress symptoms and nursing staff of the University Hospital Getúlio Vargas (HUGV). We conducted a field research, epidemiological, cross-sectional study with a quantitative approach, by the nursing staff (nurses, nursing technicians and nursing assistants) active in the surgical clinic, using sociodemographic questionnaire and the Inventory of Stress Symptoms Lipp (ISSL). In the population studied, there was a predominance of female sex workers, the majority of technical professionals in nursing and nursing assistants, the amount of nurses was not significant. A part of the population is affected by stress, the resistance stage, setting them on the verge of a pathological alteration. Most features in stress. Physical symptoms were more frequent. The weekly workload in the hospital was the main factor for the onset of stress.
Keywords: Enfermagem; Estresse; Esgotamento profissional; CIÊNCIAS DA SAÚDE: ENFERMAGEM